Global advertising in the 21st century - Vardar, Nükhet (Henry Stewart Talks, 2020)
How globalization was formed and developed, The changing face of globalization, The inception of global advertising, Advantages and disadvantages of global advertising, The role of the “Value Paradox” in global advertising